2012
DOI: 10.1073/pnas.1205990109
|View full text |Cite
|
Sign up to set email alerts
|

Gene 5.5 protein of bacteriophage T7 in complex with Escherichia coli nucleoid protein H-NS and transfer RNA masks transfer RNA priming in T7 DNA replication

Abstract: DNA primases provide oligoribonucleotides for DNA polymerase to initiate lagging strand synthesis. A deficiency in the primase of bacteriophage T7 to synthesize primers can be overcome by genetic alterations that decrease the expression of T7 gene 5.5, suggesting an alternative mechanism to prime DNA synthesis. The product of gene 5.5 (gp5.5) forms a stable complex with the Escherichia coli histone-like protein H-NS and transfer RNAs (tRNAs). The 3′-terminal sequence (5′-ACCA-3′) of tRNAs is identical to that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…Even more intriguing is our recent finding that the T7 DNA primase, under circumstances where it cannot itself synthesize RNA primers, can use preformed oligonucleotides and even tRNA as primers for lagging strand DNA synthesis (24). In this reaction, 3Ј-sequences in the oligonucleotides complementary to those in the primase recognition sequence are annealed to the primase recognition sequence and are extended by T7 DNA polymerase.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Even more intriguing is our recent finding that the T7 DNA primase, under circumstances where it cannot itself synthesize RNA primers, can use preformed oligonucleotides and even tRNA as primers for lagging strand DNA synthesis (24). In this reaction, 3Ј-sequences in the oligonucleotides complementary to those in the primase recognition sequence are annealed to the primase recognition sequence and are extended by T7 DNA polymerase.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrolysis of RNA-terminated Flaps by gp6-We recently reported that under certain circumstances, preformed oligonucleotides and even tRNA could serve as primers for T7 DNA polymerase in conjunction with the 56-kDa T7 gene 4 primase/ helicase (24). The functional oligoribonucleotides synthesized by the T7 DNA primase are pppACCC, pppACCA, and pppACAC.…”
Section: Stimulation Of Gp6 Activity By T7 Gene 25 Ssdna-bindingmentioning
confidence: 99%
See 2 more Smart Citations
“…H-NS binds to double-stranded DNA, particularly bent or curved DNA; condenses the DNA; and results in global gene regulation (283). Almost 20 years, later Bin Zhu and colleagues in my lab (240) identified mutations in gene 5.5 that allowed T7 phage, which lacked the ability to synthesize RNA primers, to nevertheless grow in E. coli. Subsequent studies revealed that gene 5.5 protein binds to E. coli transfer RNA (tRNA) and that this complex sequesters the H-NS protein.…”
Section: T7 Gene 55 Protein E Coli H-ns and Transfer Rna Primingmentioning
confidence: 99%